2015
DOI: 10.1007/s00374-015-1022-3
|View full text |Cite
|
Sign up to set email alerts
|

Invasive slug pests and their parasites—temperature responses and potential implications of climate change

Abstract: It is generally accepted that climate change is likely to disrupt host-parasite relationships, but little consideration has been given to how this may affect agricultural pests. Here, we study the potential influence of climate change on the pest slug Deroceras reticulatum and its nematode parasite Phasmarhabditis hermaphrodita. The European slug D. reticulatum is a major pest of agriculture and has become invasive in many countries throughout the world, including the Americas, Asia and Australasia. P. hermaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…10) Our results also support previous findings by Wilson et al 9) about the optimum population growth temperature range of P. hermaphrodita, which is between 12 and 18°C, since in the WW plots, the mean daily minimum and maximum temperatures were 11.3°C and 16.2°C, respectively, within a range of extreme values of 10.1 and 18.5°C. In the NW plots, the mean daily minimum temperature was 6°C, with an extreme value of 2.2°C, and it has been shown that the reproduction of P. hermaphrodita decreases significantly below 10°C.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…10) Our results also support previous findings by Wilson et al 9) about the optimum population growth temperature range of P. hermaphrodita, which is between 12 and 18°C, since in the WW plots, the mean daily minimum and maximum temperatures were 11.3°C and 16.2°C, respectively, within a range of extreme values of 10.1 and 18.5°C. In the NW plots, the mean daily minimum temperature was 6°C, with an extreme value of 2.2°C, and it has been shown that the reproduction of P. hermaphrodita decreases significantly below 10°C.…”
Section: Discussionsupporting
confidence: 81%
“…In the NW plots, the mean daily minimum temperature was 6°C, with an extreme value of 2.2°C, and it has been shown that the reproduction of P. hermaphrodita decreases significantly below 10°C. 9) Thus, while in the WW plots, there were good conditions for the multiplication of P. hermaphrodita, in the NW plots, the population growth of nematodes should have been much more limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations